Pendampingan Branding Sebagai Aktivitas Pemasaran UMKM Sari Buah Maja Di Kelurahan Bendogerit Kota Blitar - Althafahreza Citra Zeptavio; Rahman Amrullah Suwaidi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Bendogerit Village is one of the villages in the Sananwetan sub-district, Blitar City. In its development, UMKM experience problems in introducing these businesses to the wider community. The 30 KKN-Thematic group students in this case took the initiative to provide assistance to one UMKM that had just been established, namely the UMKM Sari Buah Maja. Branding assistance in the form of making logo and packaging designs to build a brand image, creating social media as a forum for these UMKM actors to market their products, creating content to attract consumer interest, and providing counseling regarding the importance of building a brand image for the products or services to be offered . Marketing activity assistance activities for UMKMs are very effective in increasing UMKM business capabilities. Assistance in building product branding makes the UMKM development process easier and UMKMs more confident in doing so.